What rates of change are needed? - Cooke, R.D. (Technical Centre for Agricultural and Rural Cooperation, 2000)
Before leaving CTA in late March 2000 to take up his new post as Head of the Technical Advisory Division at the International Fund for Agricultural Development in Rome, Italy, Dr Cooke shared some insights into institutions and change with Spore.You...